Interfacial engineering of ZrO2 metal-insulator-metal capacitor using Al2O3/TiO2 buffer layer for improved leakage properties. Issue 3 (3rd July 2022) - Shin, Heecheol; Choi, Hyobin; Lim, Jaeseong; Lee, Wanggon; Mohit, Kumar; Kim, Younsoo; Jung, Hyung-Suk; Lim, Hanjin; Seo, Hyungtak
ABSTRACT: The continuous scale-down of dynamic random-access memory (DRAM) requires shrinkage of high aspect ratio metal-insulator-metal (MIM) capacitance along with the successful suppression of its leakage current to maintain desired levels of charge storage and retention. As the dimensions of stacked insulating dielectric and metal electrodes in the MIM capacitor are currently <10 nm, interfacial mixing has a large impact on the reliability of the capacitor. This is because defects and secondary interface oxides significantly alter the physicochemical properties of MIM capacitors. The methodology required to characterize ultrathin interfaces in relation to the performance of MIM devices is highly challenging due to its physical and chemical complexities of interface between dielectric and electrode. In this study, a ZrO2 -based dielectric film and its interface (with an ultrathin TiO2 /Al2 O3 buffer layer) are analyzed using angle-resolved X-ray photoelectron spectroscopy (ARXPS), spectroscopic ellipsometry (SE), and temperature dependent I–V analysis for a DRAM MIM capacitor. The composite dielectric layer included either Al2 O3 on the bottom or Al2 O3 /TiO2 between the TiN electrode and ZrO2 . This study suggests an effective metrology approach to characterize ultrathin MIM capacitors and the important role of interfacial stabilization using a buffer layer for the effective control of leakage current.